3D freeze printing of functional aerogels - Tetik, Halil (Kansas State University, 2022)
Aerogels are a class of highly porous materials made from almost any material compositions. The exotic properties of the aerogels including low thermal conductivity, transparency, flexibility, extremely high porosity, low weight and density, large surface area, etc. attracted the attention of many researchers working in various fields. Incorporating 3D printing technology in aerogel fabrication provided a great freedom in the design of the final product as well as a great capability of tailoring the materials properties. Yet, the 3D printing methods used for fabrication of aerogels suffer from the printability requirements, lack of appropriate support material that can be removed without harsh chemical/thermal post-processes, and lack of ability to simultaneously engineer the macrostructure of the aerogels along with their microstructure. 3D Freeze Printing (3DFP), developed by our group, has shown a great promise to address those issues in our previous studies. However, our group’s previous process investigation studies relied on only optical imaging techniques, which provided information on the material deposition, but not the solidification step. This limits the depth of information that we have about the process since solidification is a very important step. Besides, feasible materials for 3DFP method were limited with graphene and silver nanowires. Considering the wide range of materials used for 3D printed aerogels, different materials need to be introduced to 3DFP method to realize its full potential in the area. In addition, , a fully functioning device using 3DFP method has never been built and evaluated for its performance compared to the devices fabricated by other methods. Moreover, there is a need for a fabrication method which can fabricate aerogels with non-monolithic predesigned microstructures (e.g. pores of various sizes located in certain regions of the aerogels), especially for applications in the field of controlled drug-delivery, bone tissue engineering, selective liquid sorption, and so on. In this thesis, based on the motivation listed above, 3DFP method has been studied in the course of realizing its full potential in the field. Firstly, a process investigation has been performed to simultaneously observe the material deposition and solidification (freezing) using the sophisticated X-ray imaging facilities in SLAC National Accelerator Laboratory. This investigation helped to develop a mathematical model for the geometry of the deposited material, observe the material deposition and solidification concurrently, and understand the effects of different process parameters (e.g. jetting frequency, print head speed, and substrate temperature) on the phase change as well as the quality of the printed constructs. Then, aerogels based on novel materials (cellulose nanocrystals (CNC) and MXenes) for 3DFP method were fabricated and characterized. By incorporating different additives in the ink formulation, different functionalities have been achieved for 3D printed CNC aerogels. Functional devices were developed using the 3D printed MXene aerogels, an enhancement in their performance was achieved by engineering the microstructure, and eventually their performance was compared with other reported devices fabricated by different methods. Finally, a novel method for fabrication of aerogels having non-monolithic micropore morphologies was developed. By achieving local temperature gradients on the substrate used for unidirectional freeze casting and 3DFP processes, a predesigned microstructure where the location of large and small pores can be precisely controlled is obtained. This method has a great potential for applications such as drug delivery, bone tissue engineering, photo catalysis, selective absorption, etc. where a predesigned non-monolithic micropore morphology can be an asset.
Keywords: Additive manufacturing; 3D printing; Aerogels